Non-invasive measurement of progesterone and cortisol metabolites in the faeces of captive female Rusa unicolor at Zoo Negara, Malaysia and its reproductive and stress behaviour - Abdul Hamid, Noor Haida; Mohd Nadzir, Mohd Noor Hisham; Omar, Junaidi; Annavi, Geetha; Wan Jaafar, Wan Nor Fitri; Salleh, Annas (Universiti Putra Malaysia Press, 2022)
Sambar deer are listed as vulnerable and are bred in captivity under governmental management. The success of captive breeding programs varies, and the underlying causes are unclear. The advantage of using non-invasive faecal samples to obtain hormonal profiles without the animal being sedated or restrained has not been tested in sambar deer. This experiment was aimed to study the reproductive and stress behaviours of sambar deer and to measure the levels of reproductive and stress hormones in captive female sambar deer via a non-invasive procedure using faeces samples. Data on reproductive and stress behaviour were collected from six sambar deer for six months. Behaviours were recorded by instantaneous sampling method using direct observation. The reproductive and stress hormones in faecal samples were analysed using ELISA procedures. There are differences in frequency of certain reproductive behaviours recorded within different sessions of data collections while stress behaviour was in the low count and no huge difference in frequency between different sessions. Progesterone metabolites showed some trend of high concentrations in July and started to drop at the end of July till the end of December with constantly negative concentrations. Sambar deer in Zoo Negara can be considered not in stress due to low reading of cortisol concentration even though there was a presence of visitors. In future, it is important to make sure the faecal samples for hormonal analysis are collected daily to look for the pattern of the oestrus cycle in sambar deer.